Polyploid evolution: The ultimate way to grasp the nettle - Rejlová, Ludmila; Chrtek, Jindřich; Trávníček, Pavel; Lučanová, Magdalena; Vít, Petr; Urfus, Tomáš (PloS one, 2019)
Polyploidy is one of the major forces of plant evolution and widespread mixed-ploidy species offer an opportunity to evaluate its significance. We therefore selected the cosmopolitan species Urtica dioica (stinging nettle), examined its cytogeography and pattern of absolute genome size, and assessed correlations with bioclimatic and ecogeographic data (latitude, longitude, elevation). We evaluated variation in ploidy level using an extensive dataset of 7012 samples from 1317 populations covering most of the species' distribution area. The widespread tetraploid cytotype (87%) was strongly prevalent over diploids (13%). A subsequent analysis of absolute genome size proved a uniform Cx-value of core U. dioica (except for U. d. subsp. cypria) whereas other closely related species, namely U. bianorii, U. kioviensis and U. simensis, differed significantly. We detected a positive correlation between relative genome size and longitude and latitude in the complete dataset of European populations and a positive correlation between relative genome size and longitude in a reduced dataset of diploid accessions (the complete dataset of diploids excluding U. d. subsp. kurdistanica). In addition, our data indicate an affinity of most diploids to natural and near-natural habitats and that the tetraploid cytotype and a small part of diploids (population from the Po river basin in northern Italy) tend to inhabit synanthropic sites. To sum up, the pattern of ploidy variation revealed by our study is in many aspects unique to the stinging nettle, being most likely first of all driven by the greater ecological plasticity and invasiveness of the tetraploid cytotype.
Keywords: Asia, Western; Ploidies; Europe; biologická evoluce; Geography; karyotypizace; Genome, Plant; Karyotyping; selekce (genetika); Evropa; Genome Size; fyziologická adaptace; ploidie; délka genomu; zeměpis; Selection, Genetic; Adaptation, Physiological; ekosystém; Ecosystem; Biological Evolution; genom rostlinný; Urtica dioica; západní Asie